Development of a Metal Oxide Cathode Catalyst for Aircathode Microbial Fuel Cells - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
Microbial fuel cell (MFC) converts the organic compounds to electricity. The higher cost of the cathode catalyst for oxygen reduction reaction (ORR) is one of the major limitations in the technology. Therefore, the study endeavored to introduce a novel cathode catalyst i.e. porous Co3O4 flakes for ORR in MFCs. The flakes exhibited the micropore surface area of 1.0372 m²/g. The MFC with cobalt oxide flakes as the cathode catalyst produced a maximum voltage of 670 mV, which was ca. 1.5 times higher than the bare electrode. In addition, the ohmic resistance was reduced ca. 3 times than the control MFC. The flakes showed a higher kinetics (6.69 A/m²) than the bare electrode (4.49 A/m²). The improved activity of the cobalt oxide flakes can be attributed to its porous surface that provided more active sites for the oxygen, consequently, resulted the faster ORR kinetics.